Multiple regression with discrete dependent variables - Orme, John G.; Combs-Orme, Terri (New York ; Oxford : Oxford University Press, 2009)
This volume presents detailed discussions of regression models that are appropriate for a variety of discrete dependent variables. Clear language guides the reader briefly through each step of the analysis, using SPSS and result presentation to enhance understanding of the important link function.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Statistical methods; Regression analysis